Executive functions and attachment to mother and father in inpatient female and male adolescents. Issue 1 (2nd January 2020) - Gambin, Malgorzata; Wozniak-Prus, Malgorzata; Sharp, Carla
ABSTRACT: The aim of the current study was to investigate relations between executive function behaviors and attachment to both mother and father separately in adolescent girls (n = 222) and boys (n = 136) in order to identify key dimensions of parent-child relationship quality that may play a role in the development and treatment of executive function deficits in adolescence. Adolescents were interviewed with the Child Attachment Interview. Parents completed the Behavior Rating Inventory of Executive Function. Results demonstrated that females with insecure attachment representations of their fathers (in particular preoccupied attachment representations) displayed more executive function difficulties in comparison to females with secure attachment representations. Executive functioning was not related to attachment organization in boys. Our results emphasize the importance of exploring various pathways for the development of attachment and executive functions in girls and boys and for gaining a better understanding of the representational dynamics of father-daughter relationships.